¿Las Asociaciones Público-Pivadas en el Perú se alinean a los estándares internacionales?: Reflexiones a propósito de las Disposiciones Legales Modelo de la CNUDMI sobre las Alianzas Público-Privadas - Arméstar Alzamora, Claudia (2021)
Presently, the importance of infrastructure and the provision of public services is undeniable. Having successful private-public partnerships is a crucial resource for Peru. Recently, the United Nations Commission on International Trade Law issued the Model Legislative Provisions on Public-Private Partnerships, which gathers the standards and international practices for the public-private partnership development. In this article the author comments on the main recommendations proposed by the mentioned provisions and the impact they could have in project development in Peru.